Povidone-iodine in ophthalmological practice - I.A. Koroleva; Kozhukhov A.A (РМЖ "Клиническая офтальмология")
Koroleva I.A.1, Kozhukhov A.A.2 1 Municipal Clinical Hospital № 15 named after O.M. Filatov, Moscow 2 Institute for Advanced Studies of Federal Medical Biological Agency, Moscow The article considers the possibilities of reducing the risk of complications during phacoemulsification by effectively suppressing the bacterial flora in the operation area. Preoperative preparation often involves the appointment of antibiotics for several hours (in the forced mode) and / or a few days before the operation, and mandatory use of antiseptics. Antiseptic drugs, in particular different concentrations of povidone-iodine solution, have bactericidal activity with a wide spectrum of action (against bacteria, fungi, viruses, protozoa), lack of resistance to microorganisms, safety and good tolerability in local applications, and economic accessibility. According to some reports, instillation in the eye of povidone-iodine before surgery reduces the risk of endophthalmitis fr om 0.24% to 0.06%. With intravitreal injections (IVI), it should be borne in mind that this procedure can be repeated repeatedly in the same patient, and this proportionately increases the risk of complications. Reuse of local antibiotics in such a situation leads to colonization of the eye surface by bacteria with resistance to them. The only preventive measure with proven effectiveness is the use of povidone-iodine for antiseptic treatment of the eye surface before IVI. The use of povidone-iodine drugs to treat bacterial keratitis of conjunctivitis is advisable in developing countries wh ere antibiotics are inaccessible or too expensive. Key words: antiseptic, povidone-iodine, phacoemulsification, intravitreal injection, endophthalmitis. For citation: Koroleva I.A., Kozhukhov A.A. Povidone-iodine in ophthalmological practice // RMJ “Clinical ophthalmology”. 2018;1:45–49.